Analysis of the I'lal Process in Arabic Words Prior to Being Loaned to the Malay Language: (Analisis Proses I'lal Dalam Perkataan Bahasa Arab Sebelum Dipinjamkan kepada Bahasa Melayu) (Jurnal Bahasa, 2019)
This paper analyses and interprets the changes of sound contained in Arabic words prior to being borrowed by the Malay language, whereby sound changes in the study of Arabic are specifically known as the i'lal process. A study that specializes in the etymological aspects requires reference to Arabic dictionaries and a sound knowledge of word origins and root words in the source language before the i'lal process occurred. This is because the search for a word in the Arabic dictionary is based on its root word and not on the direct phonetic representation of the word. This study is aimed to expose users of the Malay language to the origins of the words in the i'lal process of the Arabic language before being loaned to the Malay language. The study employed secondary data obtained from the Mu'jam Mufradat al-Ibdal wa al-i'lal fi al-Quran al-Karim dictionary and the Malay-language corpus of DBP. This study uses the theoretical framework of moraic phonology to explain the phonological process involved in the input to its phonetic representation. This study found that the process of sound changes from the input to the output of words occurs through compensatory lengthening as a result of the processes of deletion, resyllabification, lengthening and delinking as the study is limited to researching aspects of lengthening only.Keywords: i'lal, Arabic language, Malay language, phonology, mora, phonetic representation